Potential of staphylococcus xylosus strain for recovering nickel ions from aqueous solutions - Abduh Algheethi, Adel Ali Saeed; Noman, Efaq; Radin Mohamed, Radin Maya Saphira; Abdel-Monem, Mohamed Osman; Mohd Kassim, Amir Hashim (Penerbit Akademia Baru, 2018)
The potential of bacterial biomass for the biosorption of heavy metals has investigated extensively. However, the bacterial species exhibited different affinities toward the heavy metals ions based on their differences in cell wall characteristics, structure and physiological status (living or dead cells). In this study, the potential of living and dead cells of Staphylococcus xylosus 222W for removal nickel ions from aqueous solution as a function for physiological status, nickel and biomass concentrations, time, pH and temperature was investigated. The pre-treatment of bacterial cells was performed by the heating at 100 ºC for 15 min. The removal experiments were conducted in the lab scale. The results revealed that the dead cells exhibited more efficiency in removing nickel ions than living cells at all investigated concentrations (2 to 10 mM). The biosorption efficiency (E %) increased with increasing in biomass cells to limit concentrations (0.1 to 1 g dry wt L-1). The maximum removal of nickel was 81.41 vs. 77.10 % by living and dead cells, respectively achieved after 9 and 10 hrs of the incubation period, respectively. The acidic conditions decrease the efficiency of metal removal, while the optimal removal was recorded at pH 8 for both biomass (living and dead cells). The maximum uptake capacity of S. xylosus 222W (living and dead cells) was recorded at 37oC, the percentage removed being 75.90 vs. 84.92 %, respectively. It can be concluded that S. xylosus 222W exhibited high potential and affinity to remove of nickel ions from aqueous solution.